Indium Oxide Powder Synthesis in a Low-Current Discharge Plasma at Atmospheric Pressure - Konstantin Savkin; Dmitry Sorokin; Dmitry Beloplotov; Marina Ostapenko; Viktor Semin; Efim Oks (Ceramics, 2023)
The results of a study of the processes involved in the production of indium oxide In2O3 powder, which is widely used to create transparent and electrically conducting ceramics, are described. The powder was produced in a flow of rare gas (argon or helium) at atmospheric pressure under conditions for the formation of metal-containing plasma in a non-arc discharge mode. The discharge operated in pulsed mode with a pulse repetition rate of 70 kHz and pulse duration of 12 μs. The discharge current was 670 mA and discharge voltages were 180 V and 250 V when the working gases were argon and helium, respectively. These parameters ensure a mode in which the indium cap of a molybdenum cathode suffers thermal erosion. The morphology and elemental and phase composition of the erosion products were studied using transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD) analysis. It was shown that the structure of the synthesized powder particles corresponded to a phase of indium oxide (III) with a body-centered cubic (bcc) lattice with lattice parameter a = 1.013 nm. The powder particles, regardless of the working gas (Ar or He), consisted of non-stoichiometric indium oxide In2O3 with a nanocrystalline structure. The average particle diameter was <d> = 13–16 nm.